Young African women turn to coding - Fatimatou Sene (Africa Renewal, 2018)
At Kwame Nkrumah University of Science and Technology, Angela Koranteng was an accomplished student with a special dream. At a time when few women were breaking the gender barrier in maledominated studies, Ms. Koranteng had her heart set on health sciences—but instead of treating patients, she wanted to be an engineer and build hospitals.